Microbiome alterations in women with gestational diabetes mellitus and their offspring: A systematic review - Farhat, Sara; Hemmatabadi, Mahboobeh; Ejtahed, Hanieh-Sadat; Shirzad, Nooshin; Larijani, Bagher (Frontiers in Endocrinology, 2022)
Aims: Gestational diabetes mellitus (GDM) is a metabolic disorder that might predispose pregnant women to develop type 2 Diabetes Mellitus or lead to severe adverse outcomes in their offspring. One of the factors that have been thought to be involved in the pathology behind this disorder is the microbiome. In this systematic review, we comprehensively review the documents regarding the microbiota alterations in different tracts of pregnant women with GDM and their offspring. Methods: A comprehensive search was conducted in major databases including MEDLINE (PubMed), Scopus, and Web of sciences up to August 2021. Data on the demographics, methodology, and microbiome alterations were extracted and classified according to the type of microbiome in pregnant women with GDM and their offspring. The quality of studies was assessed using the Newcastle-Ottawa Scale (NOS). Results: In 49 articles that were retrieved, the findings were variable on the level of changes in alpha and beta diversity, enrichment or depletion in phyla, genera, species, and OTUs, in each microbiome type. Although there were some inconsistencies among the results, a pattern of significant alterations was seen in the gut, oral, and vaginal microbiome of women with GDM and the gut, oral, and placental microbiome of their offspring. Conclusion: Even though the alteration of the microbiome of the different tracts was seen in the cases of GDM, the inconsistency among the studies prevents us from identifying unique patterns. However, the results seem promising and further studies that overcome the confounding factors related to the demographics and methodology are needed.